Musculoskeletal function : an anatomy and kinesiology laboratory manual - Esch, Dortha; Lepley, Marvin (University of Minnesota Press, 1974)
A basic guide to the study of kinesiology. May be used as a textbook by students of occupational and physical therapy, prosthetics, and orthotics, and as a reference for clinicians in these fields.